Determinants of Occupational Stress in Health Services: Analysis of Communication Skills and Work Units (A Literature Review) - Muhammad Dwi Satriyanto; Ratna Wardani (International Journal of Advanced Multidisciplinary, 2024)
This literature review aims to identify and analyze the determinants of occupational stress in health services, with a specific focus on the impact of communication skills and work units. Understanding these determinants is crucial for developing strategies to mitigate stress and improve the overall well-being of healthcare professionals. Methodology: A comprehensive review of existing literature was conducted, utilizing academic databases such as PubMed, Scopus, and Google Scholar. The selection criteria included peer-reviewed articles published between 2010 and 2023, focusing on occupational stress in health services, communication skills, and work unit dynamics. Thematic analysis was employed to synthesize findings from the selected studies. Results/Findings: The review revealed that poor communication skills significantly contribute to occupational stress among healthcare professionals. Ineffective communication can lead to misunderstandings, increased workload, and conflict, exacerbating stress levels. Additionally, the work unit's structure and environment, including team dynamics, leadership styles, and resource availability, were found to influence stress levels. Units with supportive leadership and cohesive team dynamics reported lower stress levels, while those with high workloads and poor resource management experienced higher stress levels. Contribution: This review contributes to the body of knowledge by highlighting the critical role of communication skills and work unit dynamics in occupational stress within health services. It underscores the need for targeted interventions to enhance communication skills and optimize work unit environments to reduce stress among healthcare professionals. Originality: This literature review provides a unique synthesis of the determinants of occupational stress in health services, specifically emphasizing the interplay between communication skills and work unit dynamics. It offers a novel perspective that can inform the development of comprehensive stress reduction strategies tailored to healthcare settings.